MOTOR ACTIVITY OF STUDENT YOUTH IN THE CONDITIONS OF DISTANCE LEARNING - Hakman, Anna; Medvid, Anzhela; Mindrescu, V; Bamburak, V; Yakobchuk, D (My University, 2022)
Modern students have a lack of motor activity. One of the reasons is the pandemic, during which classes are prohibited in gyms, swimming pools and other sports facilities. Higher education institutions have partially or completely switched to distance learning, which only increases the lack of students' motor activity. In the conditions of forced hypodynamia, maintaining physical shape is an important aspect for the prevention of physical and mental health disorders. The goal of our research is to theoretically substantiate the peculiarities of motor activity of student youth in terms of distance learning. Research methods: theoretical analysis of scientific and methodological literature, analysis, synthesis, deduction and generalization. Research findings. In the context of the introduction of quarantine measures, the basis of physical education of students are independent classes using all possible types of motor activity. Exercise daily will improve your physical and mental health, ensure the maintenance of physical fitness and strengthen your health and immune system. Distance education has the right to exist alongside full-time education and to be its logical combination and complementarity. It has significant opportunities in the steadiness and regularity of students' independent work, gives them the right to choose the type of physical culture and sports activities and free choice of time for classes, equal rights to involve students with varying degrees of health problems. One of the key disadvantages of distance learning is that for those disciplines that are mastered by future physical education teachers, it is important to control the technique, intensity of exercise and control over the physical condition and wellbeing of students. Conclusions. There are certain guidelines on which one should to rely: the quality of this type of education depends on the self-organization of the student and the desire of the teacher to improve their professional skills. Distance physical education classes help to form a more extensive theoretical baggage, promote preservation of health, motivate to a healthy lifestyle only with a high level of conscious self-organization, self-discipline and student motivation.
РУХОВА АКТИВНІСТЬ СТУДЕНТСЬКОЇ МОЛОДІ В УМОВАХ ДИСТАНЦІЙНОГО НАВЧАННЯ
Keywords: distance learning, students, motor activity